The stiffness and strength degradation of timber concrete composite slab deck under repeated loading - Yeo, Kevin Jit Tong (2021)
TCC (timber-concrete composite) is usually utilised in bridges and flooring system where they are subjected to repeated loadings during their service life, which amplifies the occurrence of fatigue. The American Society of Civil Engineers (ASCE) committee on Fatigue Fracture and Reliability states that fatigue is related to about 80 percent of structural failures among bridges. The occurrence of fatigue produces a damaging effect on the concrete, timber, and interlayer shear connectors, which ultimately causes the degradation of strength and softening of the TCC structure. However, there is still limited information available on the fatigue behaviour of TCC structures especially its effect at SLS (serviceability-limit state) and ULS (ultimatelimit